Liver Stiffness 1 Year After Transplantation Predicts Clinical Outcomes in Patients With Recurrent Hepatitis C. Issue 2 (10th January 2014) - Crespo, G.; Lens, S.; Gambato, M.; Carrión, J. A.; Mariño, Z.; Londoño, M.‐C.; Miquel, R.; Bosch, J.; Navasa, M.; Forns, X.
Abstract The value of transient elastography (TE) to assess clinical outcomes in hepatitis C recurrence after liver transplantation (LT) has not been explored so far. We studied 144 hepatitis C–infected and 48 non–hepatitis C virus (HCV)‐infected LT recipients and evaluated the prognostic value of TE 1 year after transplantation to predict clinical decompensations and graft and patient survival. In HCV patients, cumulative probabilities of liver decompensation 5 years after LT were 8% for patients with liver stiffness measurement (LSM) <8.7 kilopascals (kPa) versus 47% for patients with LSM ≥ 8.7 kPa (p < 0.001). Five‐year graft and patient cumulative survival were 90% and 92% in patients with LSM < 8.7 kPa (p < 0.001) and 63% and 64% in patients with LSM ≥ 8.7 kPa, respectively (p < 0.001). Patients with low LSM 1 year after LT had excellent outcomes independently from receiving antiviral treatment or achieving sustained virological response (SVR). In contrast, graft survival significantly improved in patients with LSM ≥ 8.7 kPa who achieved SVR. No association between outcomes and LSM at 12 months was observed in non‐HCV patients. In conclusion, LSM 1 year after LT is a valuable tool to predict hepatitis C‐related outcomes in recurrent hepatitis C and can be used in clinical practice to identify the best candidates for antiviral therapy.